KAJIAN LITERATUR MENGENAI PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Fira Sofiani Solihah; Yoyo Zakaria Ansori; Ari Yanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading skills are fundamental competencies that elementary school students must master as the foundation for further literacy development. However, various studies indicate that students’ early reading abilities in Indonesia remain relatively low, requiring effective learning strategies to overcome this challenge. This study aims to analyze the influence of the cooperative learning model type STAD on elementary school students’ early reading skills. The method employed was a literature review by examining several relevant and accredited classroom action research articles obtained through Google Scholar and the Publish or Perish application. The findings show that the implementation of the STAD model consistently improves students’ early reading skills. The improvement can be seen from the mastery level in the first cycle, which ranged from 50% to 65%, and then increased in the second cycle to 73%–90%. These results demonstrate that the STAD model not only encourages students to actively collaborate in groups but also strengthens individual accountability in the learning process. Therefore, the cooperative learning model type STAD can be considered an effective instructional strategy to enhance elementary school students’ early reading skills.